Sustaining Scholarly Infrastructures through Collective Action: The lessons that Olson can teach us - Neylon, Cameron (2017)
Infrastructures for data, such as repositories, curation systems, aggregators, indexes and standards are public goods. This means that finding sustainable economic models to support them is a challenge. This is due to free-loading, where someone who does not contribute to the support of the infrastructure nonetheless gains the benefit of it. The work of Mancur Olson (1974) suggests there are only three ways to address this for large groups: compulsion (often as some form of taxation) to support the infrastructure; the provision of non-collective (club) goods limited to those who contribute as a side-effect of providing the collective good; or mechanisms that lower the effective number of participants in the negotiation (oligopoly). In this paper I use Olson's framework to analyze existing scholarly infrastructures and proposals for the sustainability of new infrastructures. I argue that the focus on sustainability models prior to seeking a set of agreed governance principles is the wrong approach. Rather we need to understand how to navigate from club-like to public-like goods. We need to define the communities that contribute and identify club-like benefits for those contributors. We need interoperable principles of governance and resourcing to provide public-like goods and we should draw on the political economics of taxation to develop this.